Genetic factors influencing the risk of multiple myeloma bone disease - Johnson, David C.; Weinhold, Niels; Chen, Bowang; Försti, Asta; Nickel, Jolanta; Hillengaß, Jens; Bertsch, Uta; Goldschmidt, Hartmut (Leukemia, 2016)
A major complication of multiple myeloma (MM) is the development of osteolytic lesions, fractures and bone pain. To identify genetic variants influencing the development of MM bone disease (MBD), we analyzed MM patients of European ancestry (totaling 3774), which had been radiologically surveyed for MBD. Each patient had been genotyped for ~6 00 000 single-nucleotide polymorphisms with genotypes for six million common variants imputed using 1000 Genomes Project and UK10K as reference. We identified a locus at 8q24.12 for MBD (rs4407910, OPG/TNFRSF11B, odds ratio=1.38, P=4.09 × 10-9) and a promising association at 19q13.43 (rs74676832, odds ratio=1.97, P=9.33 × 10-7). Our findings demonstrate that germline variation influences MBD and highlights the importance of RANK/RANKL/OPG pathway in MBD development. These findings will contribute to the development of future strategies for prevention of MBD in the early precancerous phases of MM.